2009
DOI: 10.1016/j.ijsolstr.2009.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solution for a reinforcement layer bonded to an elliptic hole under a remote uniform load

Abstract: a b s t r a c tA general solution to a reinforced elliptic hole embedded in an infinite matrix subjected to a remote uniform load is provided in this paper. Investigations on the present elasticity problem are rather tedious due to the presence of material inhomogeneities and complex geometric configurations. Based on the technique of conformal mapping and the method of analytical continuation in conjunction with the alternating technique, the general expressions of the displacement and stresses in a reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In Nagpal et al [2] an overview of various techniques developed to reduce SCF is presented: some authors proposed, for example, removing material around the hole by using auxiliary holes or reinforcing the hole with composite material rings. Chao et al [3] obtained a general solution for a reinforced elliptic hole embedded in a matrix subjected to remote uniform load. The solution, based on the technique of conformal mapping, permits one to find the optimum design of the reinforcement layer in order to reduce stress concentration and interfacial stresses.…”
Section: Introductionmentioning
confidence: 99%
“…In Nagpal et al [2] an overview of various techniques developed to reduce SCF is presented: some authors proposed, for example, removing material around the hole by using auxiliary holes or reinforcing the hole with composite material rings. Chao et al [3] obtained a general solution for a reinforced elliptic hole embedded in a matrix subjected to remote uniform load. The solution, based on the technique of conformal mapping, permits one to find the optimum design of the reinforcement layer in order to reduce stress concentration and interfacial stresses.…”
Section: Introductionmentioning
confidence: 99%
“…A general solution to a reinforced elliptic hole embedded in an infinite matrix subjected to a remote uniform load was provided in the paper [22]. Based on the technique of conformal mapping and the method of analytical continuation in conjunction with the alternating technique, the general expressions of the displacement and stresses in a reinforcement layer and the matrix were derived explicitly in a series form.…”
Section: Introductionmentioning
confidence: 99%
“…A parametric study indicated that the SCF reduces when the Modulus of Young is progressively increased towards the center of the hole and that the angular position of maximum stress on the plate surface is unaffected by the material inhomogeneity. More recently, Chao et al [18] presented an analytical solution for the stress field at an infinity plate with reinforced elliptical hole subjected to an inclined uniform remote tensile stress. The material properties for the reinforcement material may differ from the plate properties, and the reinforcement layer is limited by two confocal ellipses.…”
Section: Introductionmentioning
confidence: 99%